Fe-catalyzed hydroxytrifluoromethylation of α-(trifluoromethyl)styrenes with CF3SO2Na: facile access to α, β-bistrifluoromethyl tertiary alcohols. Issue 47 (18th November 2022) - Zheng, Pai; Liu, Chuan; Zeng, Qianding; Zhang, Yi; Liu, Ying; He, Jingjing; Deng, Yupian; Cao, Song
Abstract : A practical Fe-catalyzed hydroxytrifluoromethylation of α-(trifluoromethyl)styrenes with CF3 SO2 Na in the presence of K2 S2 O8 and air was developed. A variety of α, β-bistrifluoromethyl tertiary alcohols were synthesized in good to excellent yields. Abstract : A mild and practical Fe-catalyzed hydroxytrifluoromethylation of α-(trifluoromethyl)styrenes with CF3 SO2 Na in the presence of K2 S2 O8 and air was developed. The reaction proceeded efficiently at room temperature without β-fluoride elimination and afforded the corresponding α, β-bistrifluoromethyl tertiary alcohols in good to excellent yields.